2012
DOI: 10.1007/s12402-012-0072-8
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and methylphenidate in children with ADHD

Abstract: Although an extensive number of studies support the efficacy and tolerability of stimulants in the treatment of attention deficit/hyperactivity disorder (ADHD), in recent years, increasing concerns have been raised about their cardiovascular safety. We investigated whether a time domain analysis of heart rate variability (HRV) recordings in 24-h ECG under medication with stimulants yielded new information about therapy control in ADHD. We analysed the HRV parameter standard deviation of all normal sinus RR int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 24 publications
3
56
0
1
Order By: Relevance
“…Animal studies have found that stimulants prolong action potential duration and resting membrane potential in sinoatrial cells (Aileru and Carpentier 1996), affect action-potential repolarization in ventricular myocytes (Casis et al 2000), affect cell membranes in the myocardium (Henderson and Fischer 1995), and have dose-related structural effects on capillary endothelial cells (Bahcelioglu et al 2009). Drug-näive children with ADHD have higher heart rates than controls (Huang and Tsai 2011;Imeraj et al 2011;Buchhorn et al 2012a) and reduced heart rate variability (HRV), which is normalized by methylphenidate (Buchhorn et al 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have found that stimulants prolong action potential duration and resting membrane potential in sinoatrial cells (Aileru and Carpentier 1996), affect action-potential repolarization in ventricular myocytes (Casis et al 2000), affect cell membranes in the myocardium (Henderson and Fischer 1995), and have dose-related structural effects on capillary endothelial cells (Bahcelioglu et al 2009). Drug-näive children with ADHD have higher heart rates than controls (Huang and Tsai 2011;Imeraj et al 2011;Buchhorn et al 2012a) and reduced heart rate variability (HRV), which is normalized by methylphenidate (Buchhorn et al 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have assessed HRV in ADHD and have shown that there is autonomic dysregulation. Studies carried out by Shibagaki and Furuya [19] , Beauchaine et al [20] , Buchhorn et al [21,22] and Musser et al [23] showed decreased vagal tone in ADHD. However, studies carried out by Börger et al [24] , Crowell et al [25] , Negrao et al [26] and Wang et al [27] show that there is parasympathetic overarousal in ADHD.…”
mentioning
confidence: 91%
“…Because of its serious side effects and possible sudden death, the F DA i s s u e d a bl a c k b o x w a r n i n g f o r methylphenidate in 2006. To minimize these side effects, a thorough cardiovascular examination should be performed and a detailed family history for cardiovascular events, including any history of sudden death, should be obtained 10 . In this study, none of the patients' relatives had any history of serious cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%